A Review of Problems Arising in the Enforcement of Business Competition Laws - Roy Marten (Legal Frontier, 2025)
Enforcement of business competition law is an important instrument in maintaining balance and fairness in the market. However, in practice, there are various problems that hinder the effectiveness of competition policy implementation. This study aims to review the issues arising in competition law enforcement, including regulatory aspects, enforcement by competent authorities, as well as challenges in the judicial process. Using a normative juridical approach and analysis of relevant cases, this study identifies the main factors that cause weak enforcement, such as lack of coordination between agencies, limited resources, and obstacles in proving cases. The results of this study are expected to provide recommendations for policy makers in strengthening the effectiveness of competition law enforcement in order to create a healthy and fair competition climate in Indonesia